2022
DOI: 10.3390/ph15060696
|View full text |Cite
|
Sign up to set email alerts
|

Analgesics Induce Alterations in the Expression of SARS-CoV-2 Entry and Arachidonic-Acid-Metabolizing Genes in the Mouse Lungs

Abstract: Paracetamol and nonsteroidal anti-inflammatory drugs are widely used in the management of respiratory viral infections. This study aimed to determine the effects of the most commonly used analgesics (paracetamol, ibuprofen, and diclofenac) on the mRNA expression of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) entry and arachidonic-acid-metabolizing genes in mouse lungs. A total of twenty eight Balb/c mice were divided into four groups and treated separately with vehicle, paracetamol, ibuprofen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…A virion is the infectious form of the virus that is released from host cells after viral replication [ 11 ]. It protects the virus genome and facilitates its entry into specific host cells, which have the required receptors or proteins that facilitate its entry [ 11 , 12 ]. The virion contains the genome, and it is surrounded by a capsid, which is made up of proteins, to protect the genome [ 13 ].…”
Section: Disease-causing Virusesmentioning
confidence: 99%
“…A virion is the infectious form of the virus that is released from host cells after viral replication [ 11 ]. It protects the virus genome and facilitates its entry into specific host cells, which have the required receptors or proteins that facilitate its entry [ 11 , 12 ]. The virion contains the genome, and it is surrounded by a capsid, which is made up of proteins, to protect the genome [ 13 ].…”
Section: Disease-causing Virusesmentioning
confidence: 99%
“…We did a pilot experiment to choose the appropriate housekeeping gene. We selected beta-actin and gapdh genes according to our previous studies [21,24]. We found that the results of gapdh were more consistent than the results of the beta-actin gene.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Briefly, 10 ng of the synthesized cDNA was added to a reaction mixture containing Luna ® Universal Master Mix (catalog number: M3003S) and 10 pmoles of forward and reverse primers. The PCR conditions used were as follows: denaturation at 95 C for 3 min followed by 40 cycles of denaturation at 95 C for 10 s and annealing at 53-58 C for 30 s [24,25]. We did a pilot experiment to choose the appropriate housekeeping gene.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…After successfully attaching the virus to the ACE2 receptor, an enzyme called protease from the host cell cleaves and activates spike glycoprotein (S) attached to the ACE2. When the attachment and activation of the spike glycoprotein (S) are completed, the virus crosses the cell wall and enters the host cell through direct fusion or endocytosis [25,26] .…”
Section: Viral Entrymentioning
confidence: 99%